2019
DOI: 10.1002/ijfe.1725
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two shocks: The dynamics of international real estate markets

Abstract: We examine the major potential drivers of five international housing markets utilizing a quantile regression approach. In particular, we investigate property market dynamics during three variant market environments, namely, under downward (bearish), normal (median), and upward (bullish) trending conditions. Monthly data series for the United States, United Kingdom, Australia, Singapore, and Hong Kong are analysed, in an attempt to quantify uncertainty and detect trading patterns for the largest securitized rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Chowdhury (2022) studied the three key and specific characteristics of banks, which enhance the transmission of monetary policy, lead to the increase in bank lending, and subsequently have a favorable (significant) impact on longer-term economic development. Regarding the effects of monetary policy on GDP (economic growth), the literature suggests economic growth promotes bank lending, and monetary policy (or tightening) negatively affects bank lending (Duan 2019;Halvorsen 2016;Bekiros 2019). Duan et al (2019) and Halvorsen and Jacobsen (2016) studied the significant effects (positive) of economic growth on bank lending, whereas Bekiros et al (2019) indicated adverse effects of the monetary policies on bank lending.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chowdhury (2022) studied the three key and specific characteristics of banks, which enhance the transmission of monetary policy, lead to the increase in bank lending, and subsequently have a favorable (significant) impact on longer-term economic development. Regarding the effects of monetary policy on GDP (economic growth), the literature suggests economic growth promotes bank lending, and monetary policy (or tightening) negatively affects bank lending (Duan 2019;Halvorsen 2016;Bekiros 2019). Duan et al (2019) and Halvorsen and Jacobsen (2016) studied the significant effects (positive) of economic growth on bank lending, whereas Bekiros et al (2019) indicated adverse effects of the monetary policies on bank lending.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the effects of monetary policy on GDP (economic growth), the literature suggests economic growth promotes bank lending, and monetary policy (or tightening) negatively affects bank lending (Duan 2019;Halvorsen 2016;Bekiros 2019). Duan et al (2019) and Halvorsen and Jacobsen (2016) studied the significant effects (positive) of economic growth on bank lending, whereas Bekiros et al (2019) indicated adverse effects of the monetary policies on bank lending. The summary figures in Table 1 imply that loan growth has a mean value of around 2%.…”
Section: Methodsmentioning
confidence: 99%
“…Uncertainty disrupts the real economy directly (e.g. output, employment, consumption, investment) and the financial markets, as well (see, among others, Alessandri & Mumtaz, 2019;Bekaert et al, 2013;Bekiros et al, 2020;Bernanke, 1983;Bloom, 2014;Carriero et al, 2018;Dixit & Pindyck, 1994;Han & Li, 2017;Jo & Sekkel, 2019;Jurado et al, 2015;Mumtaz & Theodoridis, 2018;Pastor & Veronesi, 2012, 2013. We choose the news-based index of EPU, which is the only economic uncertainty metric available on a daily frequency by Baker et al (2016) for two countries, namely, the United States and the United Kingdom (see also Karanasos & Yfanti, 2020, for the discussion on the relative merits of the EPU indices).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The authors claim that bank lending channel (BLC) and its structural changes over various states of intervention would have considerable effects on housing sector. Bekiros et al (2019) employing quantile regression, examine the role of monetary policy, among other important variables, on international housing price variations. The empirically quantified effects in the extant literature, however, appear to suffer measurably from the lack of modelling and non-distinction of state-dependent variable/asymmetric responses of monetary policy shocks on the housing prices.…”
Section: Introductionmentioning
confidence: 99%
“…During both recession and good times, monetary mechanism is often used as the main vehicle of transmission medium that translates impulses from policy into effective response of the real economy, particularly, the housing sector. Despite a robust body of work, significant ambiguity persists on the relative (in)effectiveness of policy in this sector because there is a visible mismatch of the expected heat of policy intervention with that of the actual responses (Bekiros et al, 2019; Duan et al, 2019). Duan et al (2019) exploits spatial interdependent dynamics and show that macroeconomic policy interventions have somewhat subdued effect on housing sector when spatial contiguity with respect to knowledge spillover is accounted for.…”
Section: Introductionmentioning
confidence: 99%